Effects of activating content schemata on pre-reading stage: A case study at Co Do high school in Can Tho city - Tran, Thi Kim Thi (Cantho University, 2014)
Aimed to examine the effects of content-schemata activating activities on pre-reading stage and to obtain insights into learners' attitudes towards the activities used int he study